2021
DOI: 10.1186/s12879-021-06189-2
|View full text |Cite
|
Sign up to set email alerts
|

Self-collected versus clinician-collected cervical samples for the detection of HPV infections by 14-type DNA and 7-type mRNA tests

Abstract: Background HPV self-sampling has been widely supported by the scientific community following a strong body of literature on the subject. Self-sampling is important in cervical cancer screening as it has been shown to improve participation. It is well documented that HPV-testing has proven superior to cytology with regards to sensitivity in detection of CIN and cancer. The value of self-collected samples is reliant on the quality of the molecular testing performed, as well as the patients’ prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Another important aspect is the higher rate of HPV DNA‐positive cases identified in our study compared to E6/E7 mRNA cases. An earlier study also showed that only one‐third of HPV‐DNA positive women had overexpression of mRNA E6/E7 40 . These may be transient cases that get spontaneously reverted and are not likely to progress to invasive cancer.…”
Section: Discussionmentioning
confidence: 94%
“…Another important aspect is the higher rate of HPV DNA‐positive cases identified in our study compared to E6/E7 mRNA cases. An earlier study also showed that only one‐third of HPV‐DNA positive women had overexpression of mRNA E6/E7 40 . These may be transient cases that get spontaneously reverted and are not likely to progress to invasive cancer.…”
Section: Discussionmentioning
confidence: 94%
“…HPV self-collecting is a new technique invented in recent years and has been widely supported because of the positive effect on the patients’ preference in sampling procedure and compliance to follow up on positive test results. 37 What’s more, male HPV self-collecting in genital area is much easier than females in vagina and cervix.…”
Section: Discussionmentioning
confidence: 99%
“…Women in LMICs have expressed a preference for providing vaginal swabs rather than urine for STI testing, and they prefer to self-collect their samples rather than having a healthcare provider doing so [2 ▪ ,29,30]. Crucially, multiple studies have shown strong agreement between results from self-collected versus clinician-collected samples [31,32].…”
Section: Considering Patient and Health Provider Needsmentioning
confidence: 99%